Dosis de microorganismos eficaces activados en el rendimiento de Pennisetum sp. Cuba 22. San Juan Bautista – Perú - Peña Garcia, Carlos Martin (2025)
The use of environmentally friendly products such as effective microorganisms is a way to contribute to providing quality food for polygastric animals in the Peruvian Amazon as it contributes to the maintenance of biodiversity and the University of the Peruvian Amazon with the Faculty of Agronomy presents the research entitled "DOSES OF EFFECTIVE ACTIVATED MICROORGANISMS IN THE YIELD OF Pennisetum sp. CUBA 22. SAN JUAN BAUTISTA - PERU ". A randomized complete block design was used with 5 treatments and 4 replications, with the following treatments T0 (0 cc of activated EM-1 / liter of water) T1 (50 cc of activated EM-1 / liter of water), T2 (100 cc of activated EM-1 / liter of water), T3 (150 cc of activated EM-1 / liter of water) and T4 (200 cc of activated EM-1 / liter of water), reaching the following conclusions. Research with effective microorganisms in Pennisetum sp. grass. Cuba 22 cultivar, the following results were obtained: There are two statistically equal treatments: T4 (200 cc of activated EM-1/liter of water) and T3 (150 cc of activated EM-1/liter of water), with green matter levels of 4.31 kg/m2 and 4.15 kg/m2, dry matter levels of 0.95 kg/m2 and 0.91 kg/m2, leaf weights of 1.72 kg/m2 and 1.66 kg/m2, and stem weights of 2.58 kg/m2 and 2.49 kg/m2. Regarding yield, treatment T4 (200 cc of activated EM-1/liter of water) achieved 43,100 kg/ha, and T3 (150 cc of activated EM-1/liter of water) achieved 41,500 kg/ha.